Parallel Korpus Prizmasi Tahlilida Tarjima Asarlarda Asliyat Muammosi Tadqiqi (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article talks about corpus linguistics, in particular parallel corpus, which is currently one of the most developed fields in world linguistics. The artistic text and its translated text in another language contain ideas about the difficulties that arise in the translation process. In particular, changes in the delivery of the original to readers of other languages in the source language and translation texts are covered in detail.